Influencia de la inteligencia artificial en el sistema ordinario de la Justicia Estatal. - Pasto Corregidor, Fabián Duberli (2024)
The purpose of this research is to conduct an analysis of the "Influence of artificial intelligence on the ordinary justice system"; the advantages stemming from its use, but above all, the both negative and positive effects and consequences resulting from its utilization. It is evident that in the current ever-changing world, the influence of artificial intelligence and machine learning technologies in various aspects of life has raised concerns about possible unfair or discriminatory behaviors exhibited by these systems. Several studies have highlighted the prevalence and harmful effects of biases and equity issues in artificial intelligence, especially in critical areas such as sentencing decisions in the justice system. The application of artificial intelligence technology can effectively analyze historical records, summarize laws, and legislation; however, concerns about the ethical implications of using artificial intelligence in judicial procedures are currently under scrutiny. Critics raise doubts about the ethical implications of using artificial intelligence, especially regarding the data and algorithms involved in legal decision-making processes. In this sense, the discussion surrounding the use of artificial intelligence in judicial procedures has sparked intense legal and ethical debate. Critics have raised questions about the implications of using artificial intelligence, so it is the aspect that the present research focuses on. As the influence of artificial intelligence expands in the legal system, it becomes imperative to conduct investigative analysis detailing its implications, limitations, and possibilities to shape a more just and equitable society. This critical analysis becomes increasingly necessary to understand how artificial intelligence can contribute to the 5 construction of a fairer and more effective justice system. It is imperative to ascertain whether legislations worldwide are legally prepared to address potential legal issues that may arise from the use of artificial intelligence. Furthermore, it is crucial to highlight whether there is regulation of the parameters and limitations of its use in the ordinary state system. The research methodology is qualitative, employing the dogmatic and interpretative method of constitutional and legal norms. Through these methods, a response to the problem under study is provided based on the best possible reconstruction permitted by the legal material available. Additionally, since the facts or social phenomena studied in this work are measurable and quantifiable, I will measure and establish causal relationships between variables to explain the problem under study and the current social reality. Keywords: Artificial intelligence, justice system, legality, innovation, technology, legal security, legislation.